Continuous enteral nutrition in ICU is not continuous - Williams, T.; Leslie, Gavin; Dobb, G.; Mills, L.; Leen, T. (Elsevier, 2012)
Enteral nutrition (EN) is preferred method for feeding patients unable to eat in the intensive care unit (ICU). Interruption to feeding is likely to be a major contributor to patients not receiving their prescribed nutrition goals. We aimed to develop and test strategies to reduce interruptions to EN. A prospective before (May–November 2009) and after (March–September 2010) study was conducted. Patients admitted to the 22-bed ICU of a tertiary-referral teaching hospital and who were eligible to receive EN (except cardiac surgery) were recruited. Ethics Committee approval was obtained. Baseline data were collected to identify interruptions to EN. Multidisciplinary teams led by ICU EN champions, skilled nurses who became expert in the evidence-based guidelines and practice changes, developed interventions to improve practice. These included a revised feeding guidance and changes to the management of patients weaning from mechanical ventilation and having procedures. Staff were provided with an education package and data were collected prospectively for 6 months after the practice changes. Of 652 eligible patients, the majority (79%) were fed within 24 hours. Patients fed for more than 24 h had more interruptions (median 3 [IQR 2–5] pre-intervention compared to 2 [IQR 1–4] post-intervention, p = 0.04) during the first 28 days of feeding. Reasons for interruption included weaning or removal from mechanical ventilation (29%), procedures (36%) and gastrointestinal issues (12%). A targeted strategy to improve EN practice resulted in a reduction in the number of interruptions to feeding.